PENGARUH KOMPOSISI MEDIA TANAM TERHADAP PERTUMBUHAN BIBITKAKAO (Theobroma cacao L.) - Farhan Maulana; Rosmalinda; Sopiana (Journal of Agro Plantation (JAP), 2026)
Cocoa (Theobroma cacao L.) is a highly strategic plantation product because it can increase farmers' incomes, create jobs, drive agro-industrial growth, and serve as a non-oil and gas foreign exchange source for Indonesia. This study aims to determine the effect of providing the lowest composition of planting media that produces vegetative growth of cacao seedlings (Theobroma cacao L.) equivalent to the control. This experiment was conducted on experimental land in Sukaharja Village, Ketapang Regency, West Kalimantan, from March to June 2025. The design used is a completely randomized design consisting of five replications and four treatments of planting media composition, namely K0: PMK soil: rice husk charcoal + vermicompost (1:1 + 300 g), K1: PMK soil: rice husk charcoal + vermicompost (1:1 + 200 g), K2: PMK soil: rice husk charcoal + vermicompost (2:1 + 300 g), and K3: PMK soil: rice husk charcoal + vermicompost (2:1 + 200 g). The observation parameters are seedling height, stem diameter, leaf count, seedling dry weight, and chemical properties influenced by the composition of the planting media. The growing media composition of PMK soil: rice husk charcoal + vermicompost (1:1 + 200 g) showed the lowest composition, resulting in growth similar to the control treatment.